2009
DOI: 10.1007/s00415-009-5006-9
|View full text |Cite
|
Sign up to set email alerts
|

Rechallenge with temozolomide in patients with recurrent gliomas

Abstract: Temozolomide (TMZ) is the standard of care for patients with newly diagnosed glioblastoma (GBM) as well as those with recurrent anaplastic glioma (AG) and GBM. It has become common practice to re-expose patients to TMZ who had been previously treated with TMZ, or to switch patients to alternative dosing regimens of TMZ when there are signs of relapse or progress on standard TMZ therapeutic regimens. To date, however, there is a scarcity of data on the efficacy of this therapeutic strategy, currently referred t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 16 publications
(19 reference statements)
2
59
0
3
Order By: Relevance
“…[51][52][53] In vivo evidence for the direct involvement of MGMT in the response of glioblastoma to alkylating agents has been provided by The Cancer Genome Atlas. 54 The value of temozolomide in the setting of recurrent glioblastoma, including its relationship with MGMT promoter methylation status, must now to be determined in patients who have already been exposed to temozolomide in the first-line setting, 55,56 as is being pursued in the DIRECTOR trial (http://clinicaltrials.gov, NCT00941460).…”
Section: The Role Of Mgmt In Glioma Subtypes Glioblastomamentioning
confidence: 99%
“…[51][52][53] In vivo evidence for the direct involvement of MGMT in the response of glioblastoma to alkylating agents has been provided by The Cancer Genome Atlas. 54 The value of temozolomide in the setting of recurrent glioblastoma, including its relationship with MGMT promoter methylation status, must now to be determined in patients who have already been exposed to temozolomide in the first-line setting, 55,56 as is being pursued in the DIRECTOR trial (http://clinicaltrials.gov, NCT00941460).…”
Section: The Role Of Mgmt In Glioma Subtypes Glioblastomamentioning
confidence: 99%
“…At entry, 22 patients were chemotherapy-naïve, 30 had received prior nimustine-teniposide, 3 had received procarbazine-lomustine-vincristine (pcv), and 9 had received lomustine-temozolomide. A retrospective review by the same authors reported a 6-month pfs of 27.7% for gbm patients rechallenged with temozolomide 70 , results that are comparable to those seen with the continuous low-dose temozolomide regimen.…”
Section: 61mentioning
confidence: 69%
“…1,5,16,26,30,55 A randomized, double-blind, placebo-controlled control trial also supported the implantation of carmustine (BCNU) wafers in tumor cavities after repeat operation. 10 Although salvage temozolomide had previously been used for recurrent GBM, 9,56,80 recent Level II evidence clinical studies in patients with recurrent GBM have demonstrated that salvage chemotherapy combining bevacizumab, an antiangiogenic agent, with cytotoxic drugs can extend progression-free survival and overall survival to 6.1 and 9.2 months, respectively. 21,75,82 Finally, emerging agents that target tumorigenesis pathways, such as new angiogenesis inhibitors and other novel agents, show promise as therapeutic options.…”
Section: Treatment Of Recurrent Hggsmentioning
confidence: 99%